Implementation of Fetal Welfare Monitoring with CTG in Third Trimester Pregnant Women at Gatot Soebroto Hospital Jakarta - Nova Hariyani (STIKep PPNI Jawa Barat, 2022)
Aims: This study aims to determine the implementation of fetal welfare monitoring in pregnant women in the III trimester carried out by midwives through the CTG / KTG examination at Gatot Soebroto Hospital Jakarta in 2022. Methods: The Cross-Sectional research design was utilized in this study, and the sample size was 35 people. Chi-square was used for univariate and bivariate analysis. Results: This study found that the variables related to implementing fetal welfare examinations using CTG were knowledgeable (p=0.000). In contrast, the unrelated variables were age n (p = 0.135), education (p=0.752), and the length of service life of the value (p=0.136). Conclusion: Relationship between knowledge and the implementation of fetal welfare monitoring using CTG / KTG in pregnant women of the III trimester, then midwives need to improve knowledge and skills to support their competence of midwives, through training, seminars, and education to a higher level.